An investigation into the specific function of the vaccinia virus :13.8 kDa protein encoded by the N1L gene - Abrahams, Melissa-Rose Hilda (Division of Medical Virology, 2024)
Vaccinia virus is the most extensively studied, prototype vertebrate poxvirus, which was used as a vaccine in the eradication of smallpox. The genome of this virus has characteristic variable termini encoding open reading frames that are not essential for virus replication in cell culture. One such open reading frame, N1L situated at the left terminal region of the neurovirulent Western Reserve (WR) vaccinia virus strain, encodes a protein 13.8 kDa in size. In vivo studies in mouse brains revealed that a recombinant virus, vGK5, tacking the expression of the 13.8 kDa protein was rendered replication deficient in the brain. An essential requirement of poxviruses for their replication is the energy molecule adenosine triphosphate (ATP). The supply of this molecule in the brain to support replication of a virus is limited due to the high-energy requirements and small energy reserves of this organ. The specific function of the vaccinia virus 13.8 kDa protein in relation to viral replication in the brain was investigated. The South African (SA) Lister vaccinia virus strain was confirmed to encode an identical N1L gene to that of the WR vaccinia virus by amplification, cloning and sequencing of the Lister N1L open reading frame. The Lister vaccinia virus and a 13.8 kDa deletion strain (vGK5) were cultivated and used to intracranially infect mice. Using a luciferin/luciferase bioluminescence assay system the ATP levels in Lister and vGK5 vaccinia virus-infected mouse brains were measured and found to differ significantly after a 5-day infection period. The SA vaccine Lister vaccinia virus strain was found to be a slow growing virus in the brain. Subsequently, a possible role for the vaccinia virus 13.8 kDa protein in influencing ATP levels in the brain was postulated, yet a neurovirulent wild type strain is needed for further studies to consolidate this result. The 13.8 kDa protein was successfully expressed in the P. pastoris yeast expression system and positively identified by immunodetection studies.